Сприяння впровадженню електромобілів як науково-технічна інновація в галузі автомобільного транспорту - Гайкова, Т. В.; Мурашко, О. А.; Haikova, T.; Murashko, О. (ЦНТУ, 2023)
У статті розглянуто питання перспектив розвитку і поширення застосування електромобілів в Україні. Проведено аналіз та зіставлення даних статистичних звітів і аналітичних матеріалів, що характеризують стан ринків електромобілів у світі. The purpose of this study is to analyze the consequences of the implementation of the concept of market orientation on the Ukrainian market of passenger electric cars and to determine the impact of innovations on its development. It is also necessary to analyze the application of new constructive solutions in the field of road transport, which contribute to the wider introduction of electric vehicles. As of January 1, 2023, the total number of passenger electric cars registered in Ukraine is 46,830 cars. Thus, the share of electric vehicles in the total mass of vehicles in our country is about 0.5%. The main driver of the increase in the number of electric cars was economy and a higher level of environmental safety compared to diesel and gasoline cars. Ukraine prioritizes the transition to electric road transport by January 1, 2030. In 2017, the Ministry of Infrastructure of Ukraine developed a 15-year strategy for the development of electric transport in Ukraine. According to the Ministry of Infrastructure of Ukraine, as of November 1, 2021, the Ukrainian charging network for electric vehicles included 3,244 stations with 7,661 terminals. Of them, high-speed (power over 22 kW) – 1,835 units, i.e. 24%. Other 5826 units. (76%) – ordinary terminals with a capacity of up to 22 kW. The main obstacles to the wider introduction of electric vehicles are their cost, underdeveloped recharging, service and repair infrastructure, as well as an insufficient number of maintenance and repair specialists. According to analytical data, the world electric car market is facing a serious transformation. Due to a number of factors such as a jump in electricity prices in Europe, the introduction of electric car taxation, the end of subsidies, problems with the development of global charging infrastructure, a sharp increase in the prices of raw materials, in particular, lithium and nickel. As a result, as noted, the rate of growth of sales of electric cars may slow down, and in some regions may even come to nothing. Electric cars give owners the opportunity to completely abandon traditional types of fuel and save their own money, and the state to localize the sphere of regulation of the level of environmental and man-made safety in the locations of power plants.
Promoting the Introduction of Electric Vehicles as a Scientific and Technical Innovation in the Field of Road Transport
Keywords: автомобільний транспорт; інновації; електромобілі; технології майбутнього; екологічна безпека; road transport; innovations; electric cars; technologies of the future; ecological safety